The relationship between reproductive hormones with general behaviour of captive female Bornean orangutans at Bukit Merah Orang Utan Island, Perak - Nozmi, Noramira; Md Yusof, Nur Nadiah; Ithnin, Hartini; Ramli, Muhammad Fahmi; Mohd Yusof, Farida Zuraina (Faculty of Applied Sciences, 2025)
The relationship between reproductive hormones with general behaviour of captive female Bornean orangutans at Bukit Merah Orang Utan Island, Perak Managing critically endangered species in captivity, like the orangutans (Pongo pygmies), requires deep knowledge of their physiology and behavior to provide the best husbandry under human care. Progesterone and estrogen, the main hormones in the reproductive cycle, play an essential role in controlling behavior in female mammals. However, the influence of hormones on behavior in nonhuman primates, such as orangutans, is still very limited. This study investigates the impact of progesterone and estrogen in captive female orangutans at Bukit Merah Orang Utan Island, a conservation center in Perak, Malaysia. The research explores the relationship between progesterone and estradiol levels with aggressive behavior and daily activities. Fecal sampling and behavioral observation were conducted in 93 days from March 2021 until June 2021. A total of 101 fecal samples were collected from four female orangutans named Baboon (age 33), Careena (age 15), April (age 13), and Kate (age 9) for enzyme linked immunosorbent assay (EIA) via commercial kits. Behavioral observation was conducted for 337 hours via focal and scan sampling. Aggression and four daily activities were observed, which included playing, moving, resting, and feeding. Overall, the results indicate that progesterone significantly correlates with resting, playing, and aggression behaviors, while estradiol shows no significant relationship with any behaviors. A Spearman’s correlation coefficient showed a significant but moderate positive relationship between progesterone concentration and resting behavior, r[101]=0.462, p=0.006, and with playing behavior with a moderate negative relationship, r[101]=-0.439, p=0.015. A Spearman's correlation coefficient revealed a significant moderate negative relationship between aggression and the level of progesterone, r[101]=- 0.440, p=0.009. There was no correlation between estradiol and any behaviors with p>0.05. The findings of this study will enhance the knowledge of orangutan physiology and support conservation efforts by providing data that can be used to optimize the reproductive health and well-being of captive orangutans. This research is a step towards ensuring the survival of this critically endangered species by improving the conditions under which they are kept and managed in captivity.